2014
DOI: 10.1097/dcr.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Mesh Rectopexy

Abstract: P elvic organ prolapse is a spectrum of anatomic abnormalities including rectocele, enterocele, rectal intussusception, rectal prolapse, and abnormal perineal descent, which cause significant morbidity. Pelvic discomfort, chronic drainage of blood and/or mucous from the anus, fecal incontinence, and constipation/ obstructed defecation symptoms are associated with prolapse of the pelvic organs. 1 the Women's health initiative reported that 41% of women ages 50 to 79 years showed some degree of symptomatic pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Three randomised trials have shown an improvement in constipation by avoiding division of the lateral ligaments. [ 13 14 15 ] Resection of the sigmoid colon has been recommended in patients with redundant sigmoid to improve constipation. [ 9 ] However, in our study, redundant sigmoid was present in 22 out of 25 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomised trials have shown an improvement in constipation by avoiding division of the lateral ligaments. [ 13 14 15 ] Resection of the sigmoid colon has been recommended in patients with redundant sigmoid to improve constipation. [ 9 ] However, in our study, redundant sigmoid was present in 22 out of 25 patients.…”
Section: Discussionmentioning
confidence: 99%